A Mobile Training Context for In-Service Teachers: Methods of Training and Task Practice to Enhance E-Content Production Skills - Abd El Bakey, Fatma M.; Abo Shadi, Ghada I.; El-Refai, Walid Y. (International Journal of Emerging Technologies in Learning (iJET), 2023)
Mobile training is one of the modern training systems resulting from the integration of innovations in information and communication technology (ICT), which can be used to solve the problems of traditional training in educational institutions. Therefore, it is important to study the design variables of such training that enhance its effectiveness. Thus, the present study aims to design a mobile training context (MTC) and to investigate the effect of interaction between the training method, i.e., whole task (WT) versus part task (PT), and the task practice method, i.e., massed practice (MP) versus distributed practice (DP), on the skills of e-content production of 52 public education teachers in Jeddah, Saudi Arabia, through using the semi-experimental approach and the factorial design (2 × 2). Furthermore, an application-oriented knowledge test was used to measure the participant teachers’ skills through their application of 208 items related to e-content design, production, and publishing. Findings showed the effectiveness of part-task training (PTT) compared to whole-task training (WTT) and the effectiveness of the massed practice method (MPM) compared to the distributed practice method (DPM). In addition, there was a preference for the massed practice for part-task (MPPT) treatment in comparison to other treatments. This result encourages the possibility of providing a successful MTC for training in different skills. However, further research is still required to optimize the expected future potential of the mobile training context.